Unraveling the differences between pyrolytic and petrogenic sources in oiled areas of the South Atlantic: An analytical method for biliary PAHs - Lima, Antônia D.F.; Carneiro Junior, Gladston R.; dos Santos, Rafael P.; Oliveira, Jerusa M.; de Sousa, Bianca Leite C.; de Jesus, Lázaro Wender O. [UNESP]; Cavalcante, Rivelino M. (Elsevier, 2025)
Polycyclic aromatic hydrocarbons (PAHs) represent significant organic pollutants within the scope of environmental monitoring and management investigations of oiled areas. Characterized as precursors of mutagenic and carcinogenic processes, they exert a direct influence on human and environmental health. To assess the impacts of one of the largest oil spills affecting coral reefs in Alagoas, Brazil, researchers developed, validated, and applied an innovative methodology. This approach was designed to evaluate the effects of petrogenic and pyrogenic PAHs using Stegastes fuscus, a fish species commonly found in the region. This approach utilizes high-performance liquid chromatography paired with a fluorescence detector (HPLC-FD) to accurately measure PAHs in fish bile. This method analyzed six compounds whose elution occurred in the following sequence: OHNaph > OHFln > OHPhen > OHPyr > OHChr > OHBaP. The most favorable results were observed using the matrix curve, with a linear correlation coefficient exceeding 0.9800, DL ranging from 0.03 to 79.2 ng/L, QL ranging from 0.1 to 264.1 ng/L, and accuracy ranging from 86% to 96% and with RSD between 0 and 8%. To implement the methodology, specimens of the S. fuscus species were utilized, within which all target compounds were detected across all bile samples. In 2020, the compound OHNaph with minimum, maximum value of ND-21.42x104 ng/L, and average 430.65x103 ng/L, was the most frequently detected in the Japaratinga region, while in 2021, OHPyr with ND-20.57x103 ng/L, and 19.99x103 ng/L was the most prevalent, also in Japaratinga. However, the results indicate a consistent decrease in OHNaph concentrations across all sites from 2020 to 2021, whereas levels of OHBaP showed an increase during the same period. The relative abundance of bile PAHs showed that the levels of OHNaph represent the influence of the 2019 oil spill, while the sum of OH PAHs (phenanthrene, pyrene, chrysene, and fluorene) indicates a mixed-source group. Additionally, BaP reflects the impact of chronic sources in the region, allowing for the differentiation between the influence of chronic activities and the acute impact promoted by the 2019 oil spill in the area.
Keywords: Bile sample; Fish; Fluorescence determination; Metabolites; Petrogenic source; Pyrogenic source